House of Cards i Machiavelli – Frank Underwood jako przykład współczesnego księcia - Rożewska, Agnieszka (Polityka i Społeczeństwo, 2021)
The intrigue ridden series, “House of Cards” presents the story of Frank Underwood, a “whip” responsible for discipline in the Democratic Party. To follow his ambitious, he appears as a great strategist and diplomat, and demonstrates some unique skills. Unfortunately his actions always get positive results, which has a negative impact on the realism of the series. However all the manipulative techniques used by Underwood and references to “The Prince” by Machiavelli are very authentic. This paper discusses the above techniques and instruments implemented by Frank. The fact that the series is very popular and received a great response from the viewers is related to its theme and the way of presenting politics. Although there are mixed reviews when it comes to the realism shown in the “House of Cards”, the viewer seemed to be convinced of a great opportunity presented to look backstage of White House politics.